2006
DOI: 10.1254/jphs.fp0050799
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cyclosporin A on Immediate Early Gene in Rat Global Ischemia and Its Neuroprotection

Abstract: Abstract. The expressions of the immediate early genes, c-fos and c-jun, and their product proteins C-FOS, C-JUN, and P-JUN were examined in the hippocampal CA1 subfield after global ischemia and reperfusion in rats treated with cyclosporin A. More than 90% neuronal cell death was seen in hippocampal CA1 7 days after global ischemia in control animals, but only 5% cell death after ischemia was seen in the CsA-treated animals. The expressions of c-fos and c-jun mRNA in the control animals were detected with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Thus, the decrease in c-fos mRNA levels in the pharmacological control group could be a result of suppression of Ca 2+ influx by CsA directly or by the action of calcineurin on the glutamate receptor. This effect has been shown in an ischemia model in rats, where the expression of c-fos mRNA and its product proteins in the brain was inhibited by daily administration of CsA (Yamaguchi et al, 2006). Indicators of c-fos expression had been suggested as well suited for studies of CTA encoding because this gene is obviously obligatory for the formation of the gustatory memory (Lamprecht and Dudai, 1996;Swank et al, 1996).…”
Section: Discussionmentioning
confidence: 98%
“…Thus, the decrease in c-fos mRNA levels in the pharmacological control group could be a result of suppression of Ca 2+ influx by CsA directly or by the action of calcineurin on the glutamate receptor. This effect has been shown in an ischemia model in rats, where the expression of c-fos mRNA and its product proteins in the brain was inhibited by daily administration of CsA (Yamaguchi et al, 2006). Indicators of c-fos expression had been suggested as well suited for studies of CTA encoding because this gene is obviously obligatory for the formation of the gustatory memory (Lamprecht and Dudai, 1996;Swank et al, 1996).…”
Section: Discussionmentioning
confidence: 98%
“…8 After global forebrain ischemia, CSA reduced the expression of the immediate early genes c-fos and c-jun, which contribute to neuronal cell death. 3 Moreover, CSA was protective against glutamate-induced neuronal cell damage in different neuronal cell types. [9][10][11] Given the neuroprotective properties of CSA, we investigated in the present study the effects of CSA administration under excitotoxic conditions on RGC-5 cells.…”
mentioning
confidence: 98%
“…However, today there are several further indications for the use of CSA. In the last few years, it has been shown that CSA is also neuroprotective after ischemic stroke [1][2][3] or traumatic brain injury. [4][5][6] The protective properties of CSA are caused by different mechanisms.…”
mentioning
confidence: 99%
“…It has been reported that cerebral ischemia enhances expressions of c-fos and c-jun mRNA (18) and dephosphorylates subfamilies of life-span regulators prior to delayed neuronal death in the vulnerable hippocampal regions (19). In 5-min-ischemia-caused delayed neuronal death in hippocampal CA1 neurons, Akt and calcium / calmodulin-dependent protein kinase kinase-IV activities are decreased after reperfusion, whereas during induction of ischemic tolerance, Akt activity gradually and persistently increases in the CA1 neurons with transient increase in cyclic AMP responsive elementbinding protein phosphorylation (20).…”
Section: +mentioning
confidence: 99%